2007
DOI: 10.1159/000108357
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Peritoneal Dialysis Patients

Abstract: Background/Aims: Sexual dysfunction in patients undergoing peritoneal dialysis (PD) is highly prevalent, but studies addressing this issue are scarce. This cross-sectional study aims to evaluate sexual dysfunction and the determinants among PD patients. Methods: All chronic PD patients in 8 PD centers were asked to complete a self-reported questionnaire – the International Index of Erectile Function (IIEF) for men and the Index of Female Sexual Function (IFSF) for women – so that sexual function could be asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
3
23
2
2
Order By: Relevance
“…Despite a wide variability related to the method of assessing ED, similarly high prevalences had been usually reported in many other countries such as Brazil (60.3%), 13 Egypt (82.5%), 14 Morocco (81.4%), 15 and Iran (86.6%) 16 . As noticed in our patients, the occurrence of ED is independent of the dialysis method (hemodialysis vs. peritoneal dialysis) 17,18 . However, the small number of peritoneal dialysis patients (7) represents a serious limitation for a comparison with hemodialysis patients.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Despite a wide variability related to the method of assessing ED, similarly high prevalences had been usually reported in many other countries such as Brazil (60.3%), 13 Egypt (82.5%), 14 Morocco (81.4%), 15 and Iran (86.6%) 16 . As noticed in our patients, the occurrence of ED is independent of the dialysis method (hemodialysis vs. peritoneal dialysis) 17,18 . However, the small number of peritoneal dialysis patients (7) represents a serious limitation for a comparison with hemodialysis patients.…”
Section: Discussionsupporting
confidence: 70%
“…11 This 5-item questionnaire had been already validated in dialysis patients and is easier to administrate in daily clinical practice. 3,12 The possible scores for the IIEF-5 range from 5 to 25, and ED was classified into 5 categories based on the scores: severe (5-7), moderate (8)(9)(10)(11), mild to moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25). 12 We also collected data on patients' marital status, sexual activity, and paternity during dialysis treatment.…”
Section: Population Study and Data Collectionmentioning
confidence: 99%
“…Hypercholesterolemia, hyperlipidemia, hyperthyroidism or hypothyroidism, low Fig. 1 continued blood zinc, low testosterone, high prolactin, and even high parathyroid hormone are associated with ED [18,19]. The value of routine measurements of serum testosterone, prolactin, and thyroid function tests in men with erectile dysfunction is no longer a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The dialysis modality is probably unimportant. While the reported rate of ED in peritoneal dialysis patients might be lower (84), these patients are often younger than their hemodialyzed counterparts and have a lower comorbidity burden. Conversely, a number of studies have found that kidney transplantation has a beneficial effect upon sexual function in a significant proportion of patients previously treated with dialysis.…”
Section: Management Of Sexual Dysfunction In Ckdmentioning
confidence: 99%